Conceptualization of the concept of digital maturity of a university in the context of digital transformation of higher education - Galina Alekseevna Bannykh; Svetlana Nikolaevna Kostina (Вестник Майкопского государственного технологического университета)
Digital transformation as a natural stage in the development of any organization in the context of new socio-economic conditions requires the development of general models for the course of this process, as well as systems for assessing the achievement of the main indicators of digital development. In the Russian Federation the President and the Government have set the goal of achieving "digital maturity" for the higher education system as a priority area in the "Strategy for the digital transformation of the science and higher education industry". Today, many Russian universities are already developing digital transformation programs, and this requires an analysis of the current situation, understanding and ranking problems, as well as constructing and forecasting possible risks and effects.The purpose of the research is to analyze foreign and domestic theoretical sources that reveal the concept, models and methods for assessing the "digital maturity" of higher education organizations. Qualitative method of document analysis has been used as a research method.The results. The terminology in the context of researching the "digital maturity" of a university is actively developing. In relation to the concept, different approaches have been formed: biological, psychological, process, the category is comprehended both as a result and as a prerequisite for the digital transformation of universities. In the Russian Federation there is also a normative definition that determines the strategic priorities of the digital development of the higher education system. At the moment, the concept has been tested on several models for assessing the digital maturity of foreign and domestic universities, but the results also do not allow us to speak about the formed concept of this phenomenon.